BioBone – A prospective, blinded, multicenter validation study of the CD8 + terminal differentiated effector memory cells (CD8 + TEMRA cells) as prognostic biomarker for disturbed fracture healing – study design - Simon Reinke; Anja Maria Bauer; Michael Dahne; Georg Duda; Denis Gümbel; Christian Kleber; Georg Matziolis; Sven Märdian; Georg Osterhoff; Carsten Perka; Michael J. Raschke; Sebastian Rohe; et al. (Journal of Orthopaedic Surgery and Research)
Abstract Aims The BioBone consortium aims to validate circulating CD8 + TEMRA cells as a prognostic biomarker for predicting impaired fracture healing outcomes in a prospective, blinded, multicenter clinical study. The primary performance parameters are the pre-operative identification of at least 30% of patients who ultimately experience impaired healing at the first clinical endpoint, with a specificity greater than 90% to minimize the false-positive rate. Methods BioBone is a prospective, blinded, multicenter biomarker validation study designed to assess the prognostic value of circulating CD8 + TEMRA cells in fracture healing. A total of 640 patients aged 18 to 80 years with fractures of the humeral diaphysis, radial and/or ulnar diaphysis, femoral neck, trochanteric femur, femoral diaphysis, distal femur, proximal tibia, tibial diaphysis and distal tibia will be enrolled. The study is powered to validate the target assay performance and accounting for 6–7 potential confounders at an expected incidence of 10% impaired healing. Biomarker levels will be measured pre- and post-operatively using flow cytometry (FC) and patients will be monitored for one year. The primary endpoint is fracture healing status at 17–19 weeks (normal healing or delayed healing), while the secondary endpoint evaluates healing at nine months (delayed healing or pseudarthrosis). Fracture consolidation will be assessed through radiographs or computed tomography (CT) scans in conjunction with clinical assessments such as range of motion and weight-bearing capacity. Key outcome measures include radiographic analysis (RUST/RUSH scores), functional and patient-reported outcomes (e.g. weight bearing ability, range of motion, and the SF-36 questionnaire), as well as socioeconomic parameters (e.g. work capacity, rehabilitation needs, mobility). The predictive performance (sensitivity, specificity, NPV, PPV) of the biomarker will be determined in a prospective, double-blinded analysis, where CD8 + TEMRA blood levels are measured prior to surgical treatment and healing status at clinical endpoints is assessed by independent observers. Additional immunological examination and in vitro analysis of blood and fracture hematoma samples will further investigate the mechanism of action of CD8 + TEMRA cells in impaired human bone regeneration. Conclusion The BioBone study will validate the suitability of CD8 + TEMRA cells as a prognostic marker for impaired fracture healing and their integration into routine clinical practice. The results could have a global impact by incorporating immune-based prognostic tools into clinical workflows, paving the way for precision medicine approaches in trauma care. The BioBone study is funded by the German Federal Ministry of Education and Research (BMBF).